2013
DOI: 10.4236/health.2013.55113
|View full text |Cite
|
Sign up to set email alerts
|

Days of “Zero” level geomagnetic activity accompanied by the high neutron activity and dynamics of some medical events—Antipodes to geomagnetic storms

Abstract: The links of many medical-biological events with high levels of geomagnetic activity (GMA) are widely discussed. In recent years, several medical phenomena were described in inverse distribution by time with GMA. Also a concurrent to GMA and solar activity force-cosmic ray activity (CRA) and closely related high energy neutron and proton fluxes are studied as a forces dominating at low GMA and solar activity in relation to considered medical events. The aim of this study was to explore the distribution of some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Stoupel, et al, correlated increased geomagnetic activity combined with high levels of cosmic rays with increases in the number of emergencies and deaths during these periods, including increases in sudden cardiac death and cerebral strokes [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stoupel, et al, correlated increased geomagnetic activity combined with high levels of cosmic rays with increases in the number of emergencies and deaths during these periods, including increases in sudden cardiac death and cerebral strokes [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is deducted from other areas of medicine in which protons are used as a treatment tool . Additional studies of electrical heart storms are needed to delineate the mechanism of action of cosmic ray components on human health . These findings may also have implications for the development of therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Doronin et al [13] in their study that compared low-frequency geomagnetic rhythms with electroencephalogram (EEG) rhythms, blood pressure, heart rate, and reaction times, revealed that the variations in both heart and brain patterns were associated with changes in geomagnetic activity simultaneously. Stoupel et al [14] have found significant links between geomagnetic activity, accompanied by high Cosmic Ray Activity (neutron activity), and rises in more medical emergencies and total daily death number. In another study performed by this researcher [15], low GMA was associated with more sudden deaths, some increase in electrical heart instability number of ventricular and supraventricular extrasystoles and higher rate of ventricular tachycardia.…”
Section: Introductionmentioning
confidence: 99%